Two Ghosts in a House of Curriculum: Visions of the Learner and Liberal Education in Current Educational Reform* - Hammond, David (Canadian Journal of Education/Revue canadienne de l'éducation, 1992)
Notions of the “learner” and “liberal education” in a “Graduation Program” re- cently published by British Columbia’s Ministry of Education deserve a critique. Charles Taylor argues that Western practices and institutions support notions of self-identity that are, in turn, reformulations of Lockean and Rousseauian views of the moral life. I make three points. First, the Graduation Program uncritically incorporates versions of both ethics in its description of the learner. Second, in their discussion of curriculum organization and implementation, the authors aban- don the Rousseauian view and present a weak utilitarian account of the graduat- ing pupil. And third, although the latter conception might be economically or politically useful, it is educationally fatuous, especially in light of the authors’ claim that they propose “a sound, broad, and basic liberal education.” I argue that a good liberal curriculum ought primarily to produce sophisticated conversation- alists. Les notions de “learner” et de “liberal education” dans un “Graduation Program” qui apparaissent dans une publication récente du ministère de l’Éducation de la Colombie-Britannique méritent une critique. Charles Taylor affirme que les mé- thodes et institutions occidentales appuient des notions d’“auto-identité” qui sont, à leur tour, des reformulations des points de vue lockiens et rousseauistes de la vie morale. L’auteur apporte trois points. D’abord, le “Graduation Program” incorpore sans critique des versions des deux éthiques dans sa description de l’apprenant. Deuxièmement, dans leur discussion de l’organisation et de l’im- plantation du curriculum, les auteurs abandonnent le point de vue de Rousseau et présentent un faible compte rendu utilitaire de l’élève promu. Troisièmement, bien que cette dernière conception puisse être économiquement ou politiquement utile, elle est absurde d’un point de vue éducatif, surtout à la lumière du fait que les auteurs prétendent proposer “une éducation libérale de base, vaste et solide.” L’auteur soutient qu’un bon curriculum libéral devrait surtout produire des per- sonnes qui ont l’art de la conversation.